ANALISIS KUALITAS PENGAMATAN DATA PASUT BERDASARKAN PERBANDINGAN KOMPONEN PASUT DAN SIMPANGAN BAKU - Yudo Prasetyo (TEKNIK, 2008)
Tide harmonic constanta is 2 kind of constant parameters (amplitude and phase) with periodic phase fromthe truly tide in equilibrium tide. The quality of tide data processing can be look in the standard deviationvalue of tide harmonic constanta. The standard deviation value decreasing is indicate that tide dataprocessing have a good data quality processing, contrary the standard deviation value increasing isindicate that tide data processing have a bad data quality processing. Depend on range of data observationtime (1 month,3 month, 6 month and 1 year), it will compute in 7 tide harmonic constanta to compare tidedata processing quality. It will compare using amplitude and phase standard deviation which is show thetide data processing quality. This analysis have function to prove that the range of data observation timehave a significant influence in a tide data processing.